Prevalence of oral glucocorticoid usage in the United States: A general population perspective. Issue 2 (30th January 2013) - Overman, Robert A.; Yeh, Jun‐Yen; Deal, Chad L.
Abstract Objective There is little information on oral glucocorticoid use in the general US population. Previously, there have been published estimates of glucocorticoid use in countries outside of the US. This study aimed to estimate the prevalence of glucocorticoid use, duration of use, and concomitant use of antiosteoporosis pharmaceuticals in the US population age ≥20 years. Methods Data from 5 cycles (1999–2008) of the National Health and Nutrition Examination Survey (NHANES) were used to provide nationally representative weighted estimates. Oral glucocorticoids and concomitant use of antiosteoporosis pharmaceuticals (bisphosphonates, calcitonin, calcium, hormone replacement therapies, teriparatide, and vitamin D) were analyzed. Results There were 356 NHANES respondents ages ≥20 years who reported use of an oral glucocorticoid in the combined cycles between 1999 and 2008. The weighted prevalence of oral glucocorticoid use was 1.2% (95% confidence interval [95% CI] 1.1–1.4) from 1999–2008, corresponding to 2, 513, 259 persons in the US. The mean duration of oral glucocorticoid use was 1, 605.7 days (95% CI 1, 261.2–1, 950.1), and 28.8% (95% CI 22.2–35.4) of oral glucocorticoid users reported use for ≥5 years. Concomitant use of a bisphosphonate was reported by 8.6% (95% CI 5.1–11.7) of oral glucocorticoid users, and 37.9% (95% CI 31.7–44.0) reported usage of any antiosteoporosis pharmaceutical. Conclusion Based on NHANES data from 1999–2008, it is estimated that the prevalence of glucocorticoid use in the US is 1.2%, with a long duration of use and infrequent use of antiosteoporotic medications compared to other estimates.